2014
DOI: 10.1007/s10029-014-1337-2
|View full text |Cite
|
Sign up to set email alerts
|

Single incision laparoscopic totally extraperitoneal hernioplasty (SIL-TEP): experience of 512 procedures

Abstract: The SIL-TEP is safe and technically feasible. Additional studies on long-term recurrence rates are needed to confirm the safety of SIL-TEP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 27 publications
3
11
0
Order By: Relevance
“…Since the first (SPLTEP) hernia repair was reported by Filipovic-Cugura et al, 7 and there have been few related reports in the literature. [8][9][10] In this study, median VAS score on postoperative day 1 was 2 this result was comparable to previous studies of SPLTEP with tack placement or suturing [20][21][22] Although we did not com-pare the pain score of SPLTEP without fixation with that of SPLTEP with tack placement, the present study demonstrated that SPLTEP repair without fixation suturing of the mesh did not seem to be related to high levels of postoperative pain. We unfolded the mesh without fixation suturing before the preperitoneal space was deflated under direct visualization.…”
Section: Discussionsupporting
confidence: 89%
“…Since the first (SPLTEP) hernia repair was reported by Filipovic-Cugura et al, 7 and there have been few related reports in the literature. [8][9][10] In this study, median VAS score on postoperative day 1 was 2 this result was comparable to previous studies of SPLTEP with tack placement or suturing [20][21][22] Although we did not com-pare the pain score of SPLTEP without fixation with that of SPLTEP with tack placement, the present study demonstrated that SPLTEP repair without fixation suturing of the mesh did not seem to be related to high levels of postoperative pain. We unfolded the mesh without fixation suturing before the preperitoneal space was deflated under direct visualization.…”
Section: Discussionsupporting
confidence: 89%
“…Based on the current European Hernia Society guidelines, the methods of choice for the treatment of inguinal hernia are the Lichtenstein and totally extra peritoneal (TEP) repairs [12]. Lately, single incision technique (TEP-SI) is growing in popularity in hernia operations [13,14]. A number of studies comparing single-incision laparoscopic totally extra-peritoneal inguinal hernia repair with standard TEP procedure have been published in recent years [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The operative time, the rates of conversion, postoperative hospital stay, and postoperative complications in patients ≥80 years were similar to those in the patients <80 years, although patients ≥80 years were significantly at higher risk during surgery. Kim et al reported that the complication rate among their 512 SILS‐TEP procedures was 9.6 % (45/512) (), including 21 wound seromas, 18 urinary retentions, 5 hematomas, and 1wound infection. In our study, postoperative complications were seen in 12% of patients <80 years and in 14% of patients ≥80 years, but most of the complications were seromas, which needed no puncture and were treated conservatively.…”
Section: Discussionmentioning
confidence: 99%